METODE PELAKSANAAN PERKERASAN LENTUR HOT ROLLED SHEET (HRS) PADA PROYEK PEMBANGUNAN GEDUNG CREATIVE CENTER MAJALENGKA - Rohendi, Firdha Aulia Agustina; Hendrayana, Yayat (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Abstract Practical work is one of the compulsory subjects for civil engineering study program students in accordance with the curriculum at Majalengka University which is one of the requirements for the Final Project. Practical work is observing a field object so that students are expected to have the opportunity to find out about field activities directly and apply them accordingly. with theory and practice learned in college.In this case the author presents a report on submitting practical work on the Creative Center Building Project located in Pujasera, Majalengka District, Majalengka Regency with the title "Method of implementing flexible pavement on the Majalengka Creative Center Building project". This Creative Center building was built for creativity and provides facilities in the form of a Tourist Information Center (ITC), Basketball Court, Amphitheater, Skateboard, Mep Room (Mechanical Electrical and Plumbing, Art Park and Parking Area).In preparing this practical work report, the main discussion that will be carried out is regarding the method of implementing flexible pavement for the Majalengka Creative Center Building project which includes the process and work on the pavement and can better understand the stages of implementation.The use of asphalt as a binder in flexible pavement is very large, so many infrastructures always use asphalt as a material for construction. Keywords : creative center majalengka building construction project, hot rolled sheet (hrs) flexible pavement implementation method